2012
DOI: 10.1038/mp.2012.82
|View full text |Cite
|
Sign up to set email alerts
|

The membrane raft protein Flotillin-1 is essential in dopamine neurons for amphetamine-induced behavior in Drosophila

Abstract: The dopamine transporter (DAT) is the primary molecular target responsible for the rewarding properties of the psychostimulants amphetamine (AMPH) and cocaine. AMPH increases extracellular dopamine (DA) by promoting its nonexocytotic release via DAT-mediated efflux. Previous studies in heterologous cells have shown that phosphorylation of the amino terminus of DAT is required for AMPH-induced DA efflux but not for DA uptake. However, the identity of many of the modulatory proteins and the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 75 publications
4
89
0
Order By: Relevance
“…By disrupting the function of membrane rafts in DA cells, the authors elegantly showed that localization of dDAT to these sites is required for efflux but not for transport in vivo (Pizzo et al, 2013) consistent with in vitro studies (Cremona et al, 2011). These studies also demonstrated that the behavioral effects of amphetamines in the fly are mediated through DA neurons rather than another aminergic cell type (Pizzo et al, 2013; Pizzo et al, 2014).…”
Section: Plasma Membrane Transportersmentioning
confidence: 64%
See 4 more Smart Citations
“…By disrupting the function of membrane rafts in DA cells, the authors elegantly showed that localization of dDAT to these sites is required for efflux but not for transport in vivo (Pizzo et al, 2013) consistent with in vitro studies (Cremona et al, 2011). These studies also demonstrated that the behavioral effects of amphetamines in the fly are mediated through DA neurons rather than another aminergic cell type (Pizzo et al, 2013; Pizzo et al, 2014).…”
Section: Plasma Membrane Transportersmentioning
confidence: 64%
“…Efflux represents an additional functional mode in which neurotransmitter moves out of rather than into the cell (Fleckenstein et al, 2007; Sulzer, 2011). The mechanism by which this occurs is a very active area of investigation, and includes work in Drosophila described in more detail below (Pizzo et al, 2013; Pizzo et al, 2012).…”
Section: Neurotransmitter Transportersmentioning
confidence: 99%
See 3 more Smart Citations